2020
DOI: 10.1016/j.jphotochem.2019.112257
|View full text |Cite
|
Sign up to set email alerts
|

Photonic efficiency and selectivity study of M (M=Pt, Pd, Au and Ag)/TiO2 photocatalysts for methanol reforming in the gas phase

Abstract: A number of different M/TiO 2 photocatalysts, where M (the co-catalyst) = Pt, Pd, Au and Ag, are used to drive the steam reforming of methanol (MeOH) in a gas phase continuous flow reactor operated at 100 o C. The rate of H 2 production is: Pt > Pd > Au > Ag >> no metal. The photonic efficiency of Pt/TiO 2 photocatalyst is ca. 120% which suggests some of the hydrogen derives from a current-doubling reaction mechanism. The Pt/TiO 2 photocatalyst drives the steam reforming of MeOH, which generates H 2 and CO 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…This rendered direct comparison of the catalytic properties of the bare TiO 2 materials impossible in this study. Otherwise, our hydrogen production results are of the same order as those in other works [ 13 , 57 , 58 , 59 ]. As can be seen from Figure 2 , the P25-based samples gave a higher H 2 production rate than the sol–gel-based samples, irrespectively if the Pt co-catalyst was formed by hydrogen reduction or calcination.…”
Section: Resultssupporting
confidence: 87%
“…This rendered direct comparison of the catalytic properties of the bare TiO 2 materials impossible in this study. Otherwise, our hydrogen production results are of the same order as those in other works [ 13 , 57 , 58 , 59 ]. As can be seen from Figure 2 , the P25-based samples gave a higher H 2 production rate than the sol–gel-based samples, irrespectively if the Pt co-catalyst was formed by hydrogen reduction or calcination.…”
Section: Resultssupporting
confidence: 87%
“…However, as for the intrinsic properties of TiO 2 , especially the large band gap (>3.2 eV) restricts its utilization of the visible light and the high electron-hole recombination rate, its photocatalytic activity is significantly limited [39][40][41]. Michael et al reported on metal-modified TiO 2 applied in photocatalytic reforming of methanol [42]. Four different metals (Pt, Pd, Au and Ag) were selected to be combined with TiO 2 .…”
Section: Photocatalytic Reforming Of Methanolmentioning
confidence: 99%
“…Products of photocatalytic reforming of methanol on different photocatalyst (no shading: H 2 , diagonal shading: CO 2 and vertical shading: CO, adapted from Ref [42]…”
mentioning
confidence: 99%
“…Another important application of TiO 2 -based photocatalysts is based on their ability to discolor and completely decompose organic dyes contained in water. In addition, there are a number of works in which TiO 2 -based photocatalysts were used to neutralize harmful to the atmosphere gases [ 6 , 7 , 8 , 9 ]. Chemical stability, easy accessibility, nontoxicity and the ability to oxidize under the influence of radiation, allow TiO 2 -based photocatalysts to solve the main global problems associated with pollution of the environment and need for renewable energy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%